Modeling human placental biology: a review of organoid technologies - Bashi, Alaijah; Joseph, Tyana; Schuch, Viviane; Johnson, Erica L. (Frontiers in Cell and Developmental Biology, 2026)
The development of placental organoids represents a significant breakthrough in reproductive biology, offering an advanced platform for studying human placental development and function. Unlike traditional two-dimensional (2D) cell cultures, three-dimensional (3D) organoid models, such as primary trophoblast organoids (TOs), JEG-3 organoids, and stem cell-derived organoids, provide a more robust and physiologically relevant environment. These models enable researchers to mimic the human placenta’s complex architecture and cellular interactions. As a result, these advanced models promise to reveal the mechanisms underlying placental development and the associated disorders. This review compares different organoid types, highlighting their unique features and applications in studying trophoblast invasion, syncytialization, and placental barrier function. Bioinformatics approaches, particularly transcriptomic analyses, have been crucial in validating these models and identifying stage-specific markers of placental development. With challenges such as standardization issues and ethical considerations persisting, the integration of multiple organoid models, advanced technologies, and computational analyses currently provides the most comprehensive strategy for mimicking placental development across all stages in-vivo. Future directions for organoid technologies include the development of multi-organ-on-a-chip models and personalized medicine applications. This review concludes that while no single method perfectly replicates all stages of placental development, the combination of various 3D organoid models, supported by advanced technologies and computational analyses, offers the most effective approach to studying placental biology in-vivo.